Genotoxicity evaluation of the naturally-derived food colorant, gardenia blue, and its precursor, genipin. (August 2018) - Hobbs, Cheryl A.; Koyanagi, Mihoko; Swartz, Carol; Davis, Jeffrey; Maronpot, Robert; Recio, Leslie; Hayashi, Shim-mo
Abstract: Gardenia blue is widely used in Eastern Asia as a natural food colorant. To evaluate the genotoxic potential of gardenia blue, as well as genipin, the natural starting material from which it is produced, a GLP-compliant test battery was conducted according to OECD guidelines. No evidence of mutagenicity of gardenia blue was detected in a 5-strain bacterial reverse mutation assay, with or without metabolic activation; an equivocal response for genipin occurred in S. typhimurium TA97a without metabolic activation. In in vitro micronucleus and chromosome aberration assays, genipin tested positive under some test conditions; however, gardenia blue tested negative in both assays. In combined micronucleus/comet assays conducted in male and female B6C3F1 mice, exposure to genipin at doses reaching maximal toxicity (74 and 222 mg/kg bw/day for males and females, respectively) or gardenia blue tested up to the limit dose (2000 mg/kg bw/day) did not induce micronuclei in peripheral blood or DNA damage in several examined tissues. Modified ("reverse") comet assays showed no evidence of DNA crosslinking potential of either genipin, known to form crosslinks with other macromolecules, or gardenia blue. Our results indicate that consumption of gardenia blue in food products does not pose a significant genotoxic concern for humans. Highlights: Gardenia blue is a food colorant naturally-derived from geniposide and genipin. Gardenia blue and genipin were tested for genotoxicity and crosslinking potential. Genipin, but not gardenia blue, tested positive in several in vitro assays. In mice, genipin tested equivocal and gardenia blue was negative for genotoxicity. Gardenia blue color in food products does not pose a significant genotoxic risk.